Dangerous of terrorist’s activity as a base of contradiction between well developed and developing countries - Антипенко, Володимир Федорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
On the basis of analysis of the global nature of the terrorist asymmetry defines the main directions of its elimination in international law: the criminalization of acts producing terrorist conflict and international legal criminal responsibility of States.